Eight weeks of androgen priming by daily low-dose hCG injections before ICSI treatment in women with low ovarian reserve. Issue 4 (31st January 2023) - Friis Wang, N; Bogstad, J W; Pors, S E; Petersen, M R; Pinborg, A; Yding Andersen, C; Løssl, K
Abstract: STUDY QUESTION: Does 8 weeks of continuous low-dose hCG administration increase the proportion of antral follicles that reach the preovulatory state during ovarian stimulation (OS) in women with low ovarian reserve? SUMMARY ANSWER: The proportion of antral follicles (2–10 mm) that reached the preovulatory state did not increase. WHAT IS KNOWN ALREADY: The administration of androgens prior to OS might upregulate FSH receptor (FSHR) expression on granulosa cells, making follicles more responsive to exogenous FSH stimulation during OS. LH and hCG stimulate the local follicular androgen synthesis in theca cells and may be used as an endogenous androgen priming method. Exogenous priming by testosterone and dehydroepiandrosterone (DHEA) have been shown to increase the number of retrieved oocytes and live birth rate but the studies are small, and their use is associated with side effects. STUDY DESIGN, SIZE, DURATION: A prospective, paired, non-blinded single-center study including 20 women serving as their own controls conducted between January 2021 and July 2021 at The University Hospital Copenhagen Rigshospitalet, Denmark. PARTICIPANTS/MATERIALS, SETTING, METHODS: Participants underwent two identical consecutive IVF/ICSI treatments, a Control cycle and a Study cycle, separated by ∼8 weeks (two menstrual cycles) of daily injections of 260 IU recombinant hCG (rhCG). A freeze-all strategy was applied in the Control cycle. Both IVF/ICSI cycles were performed in a fixed GnRH antagonist protocol using a daily dose of 300 IU recombinant FSH (rFSH) and GnRH antagonist 0.25 mg from stimulation days 5–6. MAIN RESULTS AND THE ROLE OF CHANCE: Follicular output rate, defined as the number of follicles >16 mm on hCG trigger day divided by the antral follicle count (2–10 mm) at baseline, did not increase after 8 weeks of hCG priming ( P = 0.8). The mean number of oocytes retrieved was significantly higher after the hCG priming being 4.7 (2.8) vs 3.2 (1.7) in the Study and Control cycle, respectively ( P = 0.01). The duration of stimulation was longer in the Study versus the Control cycle ( P = 0.05), despite the use of identical hCG trigger criterion and similar diameters of the three biggest follicles on hCG trigger day in the two cycles ( P = 0.9). LIMITATIONS, REASONS FOR CAUTION: The sample size was small, and the number of oocytes retrieved was not the primary endpoint. Larger studies are needed to confirm this finding. WIDER IMPLICATIONS OF THE FINDINGS: Long-term, low-dose rhCG administration may increase the number of oocytes retrieved during IVF/ICSI in women with low ovarian reserve, but more research is needed before firm conclusions can be drawn. STUDY FUNDING/COMPETING INTEREST(S): This study was funded by an unrestricted grant from Gedeon Richter. A.P. reports personal consulting fees from PregLem SA, Novo Nordisk A/S, Ferring Pharmaceuticals A/S, Gedeon Richter Nordics AB, Cryos International, and Merck A/S outside the submitted work and payment or honoraria for lectures from Gedeon Richter Nordics AB, Ferring Pharmaceuticals A/S, Merck A/S, and Theramex and Organon & Co. Grants to the institution have been provided by Gedeon Richter Nordics AB, Ferring Pharmaceuticals A/S, and Merck A/S and receipt of equipment by the institution from Gedeon Richter Nordics AB is reported. The remaining authors have no conflicts of interest to declare. TRIAL REGISTRATION NUMBER: ClinicalTrials.gov Identifier: NCT04643925.